Role of combination bortezomib and pegylated liposomal doxorubicin in the management of relapsed and/or refractory multiple myeloma - Jatin J Shah; Robert Z Orlowski; Sheeba K Thomas (Dove Medical Press, 2009)
Jatin J Shah1, Robert Z Orlowski1,2, Sheeba K Thomas11Departments of Lymphoma/Myeloma; 2Experimental Therapeutics, Division of Cancer Medicine, University of Texas MD Anderson Cancer Center, Houston, Texas, USAAbstract: The first in class proteasome inhibitor bortezomib (B) received its initial regulatory approval for therapy of patients with multiple myeloma (MM) in the relapsed/refractory setting. Modulation of proteasome function, however, is also a rational strategy for chemosensitization, and a variety of agents have shown synergistic activity with bortezomib pre-clinically, including anthracyclines. This formed the basis for evaluation of a regimen of bortezomib with pegylated liposomal doxorubicin (PLD). PLD+B, in a phase I study, induced a predictable and manageable toxicity profi le, and showed encouraging anti-MM activity. In a recent international, randomized phase III trial, PLD+B demonstrated a superior overall response rate and response quality compared to bortezomib alone, as well as a longer time to progression, duration of response, progression-free survival, and overall survival. Sub-analyses revealed benefits in almost all clinically relevant subgroups, including several which would be considered to have high-risk disease. These findings have led to the establishment of the PLD+B regimen as one of the standards of care for patients with relapsed and/or refractory myeloma. Efforts are now underway to build on this combination further by adding other active anti-myeloma agents. In this review, we will discuss the role of PLD+B as an important addition to our therapeutic armamentarium for patients with MM.Keywords: multiple myeloma, relapsed/refractory, pegylated liposomal doxorubicin, bortezomib, Doxil®, Velcade®